Effectiveness of Cervical Proprioception Training versus Deep Cervical Extensor Training on Cervical Extensor Endurance in Patients with Chronic Non- Specific Neck Pain - Mahendran Jayaraman; Shirana Asmi Farook; R.Rishikesavan; Yu Chye Wah; Kshtrashal Singh (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Chronic neck pain (CNP) is characterized as persisting pain for more than 3 months, which has a longer expected recovery time, and is one of the individuals most common and debilitating problem. CNP has been linked to abnormalities in cervical proprioception and neck extensor endurance (NEE), two processes that are essential for preserving cervical spine function. Neck pain itself has a clear role in proprioception and neck sensorimotor control, and subsequently influence orientation. The cervical extensor muscles are considered equally important in the recovery of patients with neck pain. Cervical Proprioception Training (CPT) may have the added advantage of facilitating the deep cervical extensor muscles. Objective: To compare the effectiveness of Cervical Proprioception Training (CPT) versusDeep Cervical Extensor Training (DCET) in patients with chronic non- specific neck pain. Methods: This was a non-randomized clinical trial that was quasi-experimental in nature. The study population included factory workers in Penang patients of both sexes, aged between 30 and 50 years, diagnosed by GP with a chronic non-specific neck pain for 3 months or more. Two experimental groups, group 1 received Cervical Proprioception Training and while group 2 received Deep Cervical Extensor Training for a duration of 6 weeks. The study included a pre and post intervention assessment of muscle endurance, functional status and pain, using validated measurement tools such as the Cervical Extensor Endurance Test (CEET) , Neck Disability Index ( NDI) and Visual Analogue Scale (VAS). Results: Following 6 weeks, concerning VAS there was a statistically significant decline of VAS in the two groups with favor to the CPT group (p < 0.05) in comparison with the DCET group. In regards to the NDI levels, there was a statistically significant decline in NDI scores in the two groups with favor to the CPT group (mean decline of 13.48) in comparison with the DCET group (mean decline of 10.17). Concerning CEET levels there was a statistically significant improvement in CEET scores (p< 0.05) in the two groups with favor to the DCET group in comparison with the CPT group. Conclusion: Both groups of patients with chronic non-specific neck pain (CNNP) demonstrated similar outcomes. Both groups were found to reduce pain levels, as assessed using VAS, and enhance functional status, as evaluated using NDI and improve NEE as measured by CEET .The present study also provided evidence to support the idea that Cervical Proprioception Training and Deep Cervical Extensor Training lead to improvements in cervical extensor endurance, as measured by CEET.